Sacajawea, wilderness guide - Jassem, Kate.; Palmer, Jan. (Mahwah, N.J. : Troll Associates, 1979)
Presents a biography of the young Shoshone Indian princess who acted as interpreter and guide for the Lewis and Clark expedition.
Keywords: Sacagawea, -- 1786-1884 -- Juvenile literature; Sacagawea, -- 1786-1884.; Shoshoni Indians -- Biography -- Juvenile literature; Shoshoni Indians -- Biography; Indians of North America -- Biography; Sacagawea, -- 1786-1884.; Indians of North America -- Biography; Lewis and Clark Expedition (1804-1806)